Computational insights into the binding pattern of mitochondrial calcium uniporter inhibitor through homology modeling, molecular dynamics simulation, binding free energy prediction and density functional theory calculation. Issue 17 (21st November 2020) - Duan, Na; Gao, Zisen; Hu, Baichun; Ge, Dandan; Li, Wei; Ye, Tong; Geng, Xiaohui; Li, Xiaodong
Abstract: The mitochondrial calcium uniporter (MCU) is the critical protein of the inner mitochondrial membrane that is the primary mediator for calcium uptake into the mitochondrial matrix. Herein we built the optimal homology model of human MCU which was refined through all-atom molecular dynamics simulation. Then, the binding mode of known inhibitor was predicted through molecular docking method, along with molecular dynamics simulation and binding free energy calculation to verify the docking result and stability of the protein-inhibitor complex. Finally, density functional theory (DFT) calculation enhanced our understanding of the molecular interaction of MCU inhibitor. Our research would provide a deeper insight into the interactions between human MCU and its inhibitor, which boosts to develop novel therapy against MCU related disease. Communicated by Ramaswamy H. Sarma